2008
DOI: 10.1074/jbc.m706777200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of the N-terminal Domain in the Regulation of RIG-I ATPase Activity

Abstract: Retinoic acid-inducible gene I (RIG-I) is a cytosolic receptor that recognizes viral RNA and activates the interferon-mediated innate antiviral response. To understand the mechanism of signal activation at the receptor level, we cloned, expressed, and purified human RIG-I containing the two caspase activation and recruitment domains (CARDs) followed by the C-terminal helicase domain. We found that recombinant RIG-I is a functional protein that interacts with double-stranded RNA with substantially higher affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 41 publications
(39 reference statements)
4
56
0
Order By: Relevance
“…8). Moreover, mutation studies revealed that a lysine (Lys) residue in motif I of the RNA helicase in human LGP2 and RIG-I (Lys30 in LGP2 or Lys270 in RIG-I) are involved in signal transduction (6,17). In the motif I of Japanese flounder LGP2, Lys30 of human LGP2 appears to be conserved in Japanese flounder LGP2, where it is Lys33 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8). Moreover, mutation studies revealed that a lysine (Lys) residue in motif I of the RNA helicase in human LGP2 and RIG-I (Lys30 in LGP2 or Lys270 in RIG-I) are involved in signal transduction (6,17). In the motif I of Japanese flounder LGP2, Lys30 of human LGP2 appears to be conserved in Japanese flounder LGP2, where it is Lys33 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The DExD/H box RNA helicase domain includes two ATP-binding motifs (i.e., DExD/H box), which are also known as "Walker motif". The RNA helicase domain of RIG-I can bind to both dsRNA and ssRNA in an ATP-dependent manner (6)…”
Section: Rlrs That Bind To Viral Rnas Contribute To the Antiviral Actmentioning
confidence: 99%
See 1 more Smart Citation
“…31,34-36 (G) P-IRF-3 or P-IRF-7 homodimerize. 22,23,37,38 Either homodimer is a promoter for Type 1 interferons' genes' transcription, 37,38 resulting in increased translation and increased Type 1 interferon protein. Note however that the spectrum of Type I interferons (and other genes) induced by each homodimer is somewhat different.…”
Section: Amplification Elementsmentioning
confidence: 99%
“…A recent report identified the PolyU/UC region of the 3'-NTR of HCV as the major pathogen-associated molecular patterns of this virus (Saito et al, 2008). Recent work suggested that in the absence of RNA, RIG-I is inhibited by intra-molecular interactions between the CARD and C-terminus domains, while RNA binding strongly stimulates ATPase activity and signaling (Gee et al, 2008). RIG-I activates the mitochondria-bound protein, IPS-1/MAVS/VISA/Cardif protein (Hiscott et al, 2006) (referred to here as MAVS) through the N-terminal tandem CARD of RIG-I and the Nterminal CARD of MAVS (T. Saito et al, 2007;Vitour & Meurs, 2007).…”
Section: Interferon-stimulating Gene Pathwaysmentioning
confidence: 99%